Pendampingan Pembelajaran Lapangan Dalam Perancangan Dan Penggunaan Sistem Irigasi Tetes Pada Mahasiswa Tingkat Akhir - Negara, I Dewa Gede Jaya; Salehudin, Salehudin; Suroso, Agus; Widiyanti, Desi; Salsabila, Fera Fitri; Supriyadi, Anid; Setiawan, Ery; Wiradarma, Lalu Wirahman; Suparjo, Suparjo; Eniarti, Miko; Hidayati, Nufalia (Jurnal Gema Ngabdi, 2025)
Final-year students of the Civil Engineering Department are the spearhead of the University of Mataram's output. They need to be provided with comprehensive academic knowledge and skills to enable them to adapt to a flexible workplace. This is especially true in the current era of drought, which is a significant concern, making it crucial to provide students with the efficient use of water for crop irrigation. Therefore, final-year students need to be encouraged to undertake field-level learning to complement their knowledge and skills before completing their studies. Therefore, it is necessary to mentor final-year students in the design and use of water-efficient drip irrigation systems at the field level for a specific period of time to improve their competency until they are able to use drip irrigation in agriculture. This activity aims to mentor final-year students in the design and use of drip irrigation systems at the dryland level in Pujut District, Central Lombok Regency. The mentoring activities include site preparation, network preparation, drip irrigation network testing, and the use of drip irrigation in the planting medium. The irrigation design uses ¾-inch and ½-inch PVC pipes, factory-made Netafim (NTF) drip pipes, a 600-liter water tank as the water source, and accessories. Students were mentored through the stages of creating a distribution network, designing a drip irrigation network, testing it, and implementing it on their planting areas. The mentoring program successfully guided four final-year students and local residents, and the students were able to construct a drip irrigation network on approximately one acre of land. The students have successfully implemented the drip irrigation system.